Tinjauan Yuridis Terhadap Kasus Tindak Pidana Perdagangan Manusia Dalam Lingkup Internasional - Azzahra, Nabila Adifia; Prasetyo, Handoyo (Media Hukum Indonesia (MHI), 2024)
This research aims to find out how the juridical review in a country regarding criminal cases of human trafficking in the international scope is. This is very important to explain so that anyone knows about the legal regulations for criminal cases of human trafficking and can find out the solutions to resolve this problem. The research method used in this article is a normative legal research method which is library research, namely research on secondary data. Data collection is carried out by studying books, scientific works and works related to these problems, as well as by examining and citing data from various reference books and applicable laws and regulations. This research also uses a library research method, namely a data collection method that uses some or all of the existing data from previous researchers. This research shows that the criminal act of human trafficking is caused by several supporting factors, including: cultural factors, poverty, lack of education, environmental factors, and weak law enforcement. So, human trafficking is a criminal act that is completely contrary to the law of any country and cannot be justified for whatever reason.